Humanistic Governance and Student Development in Vocational Education - Wang, Yudong; Ramos, Kevin Arman (International Journal of Humanities and Social Science, 2026)
As vocational education in China transitions toward quality-oriented development, governance reform in higher vocational colleges has become increasingly urgent. However, institutional management continues to be shaped by performance-based evaluation systems and administrative control logic, generating tensions between accountability and student-centered development. Drawing upon person-centered theory, hierarchy of needs theory, and contemporary student engagement research, this study examines the structural conditions, relational dynamics, and practical manifestations of humanistic-oriented educational management within higher vocational contexts. Using a qualitative research design based on semi-structured interviews with administrators, teachers, and students from five vocational colleges in Inner Mongolia, the study explores how governance principles are interpreted and enacted across institutional levels. Findings indicate that dialogic governance mechanisms, emotionally supportive disciplinary approaches, and individualized developmental support systems significantly enhance students’ sense of belongingness, autonomy, competence, and sustained engagement. These practices contribute to stronger professional identity formation and internalized responsibility. Nevertheless, the persistence of metric dominance, performance-driven accountability, and uneven resource distribution constrains the long-term sustainability of humanistic reforms. Tensions remain between quantitative evaluation standards and relational care practices. In response, this paper proposes a Humanistic Governance Transformation Framework designed to integrate institutional regulation with developmental facilitation. By recalibrating accountability structures and embedding relational ethics into governance systems, the framework offers both theoretical refinement and practical guidance for advancing vocational education modernization in China.